Where Have Girls Been? Lessons Learned and Challenges in the Agenda for combating Sexual Violence in the Inter-American Court of Human Right - Ronconi, Liliana (The Age of Human Rights Journal, 2025)
In response to the alarmingly high rates of sexual violence against girls and women in Latin America, the Inter-American human rights system is developing standards and remedies to address these issues since states have already recognized their rights, but this has not been enough. This article examines the only three cases in which the IACtHR has addressed sexual violence against girls, “V.R.P., V.P.C., and others vs. Nicaragua,” “Guzmán Albarracin vs. Ecuador,” and “Angulo Losada vs. Bolivia.” It highlights some of the achievements including the concept of intersectionality, the intensified due diligence due to their status as girls, the role of combined stereotypes, and others. It also focuses on areas for ongoing improvement such as the definition of institutional violence, the application of Article 5.2 of the ACHR concerning the conceptualization of torture, and the need for transformative reparations in the prevention of violence against girls in the Inter-American Court’s approach.